The value of preoperative high‐resolution MRI with microscopy coil for facial nonmelanoma skin cancers. Issue 1 (11th July 2020) - Sheng, Meiying; Tang, Mengxiao; Lin, Wei; Guo, Lingchuan; He, Wenjun; Chen, Weixin; Li, Ke; Liu, Jianjiang; Xiao, Can; Li, Yonggang
Abstract: Background: The extent and depth of facial nonmelanoma skin cancers and the involvement of adjacent structures are critical features for surgical planning, but they are difficult to assess clinically. High‐resolution MRI (HR‐MRI) with microscopy coil may facilitate detailed evaluation of skin lesions. The authors performed this prospective study to determine the value of high‐resolution microscopy coil MRI in the preoperative evaluation of nonmelanoma skin cancer. Materials and Methods: Between October 2018 and August 2019, 16 lesions from fifteen consecutive patients with facial nonmelanoma skin cancer were evaluated using high‐resolution microscopy coil MRI about tumor extent, depth, margins, characteristic, and their spatial relationship with adjacent structures. The preoperative HR‐MRI results were compared with the intraoperative findings and with the histopathology, with special note to the depth of invasion. Results: Among the 16 lesions, HR‐MRI imaging was found to provide accurate evaluation of tumor extent, depth, and margins and determine whether there was involvement of adjacent structures. The tumor depth measured on HR‐MRI showed good correlation with histopathologic results (CCC: 0.973), and Bland‐Altman analysis finding no significant bias existed between the two measurements. All lesions except one were completely resected with primary excision. Only one lesion required further excision. During follow‐up for 3‐15 months, no tumor recurrence was observed in any case. Conclusions: HR‐MRI is an accurate, noninvasive imaging technique that can be used as preoperative evaluation tool for facial nonmelanoma skin cancer. It can accurate predict tumor depth, margins, and involvement of structure. The valuable information it provided facilitates surgeons optimize surgical planning.